EFFECT OF AQUEOUS EXTRACT OF CITRULLUS LANATUS PULP ON SCOPOLAMINE INDUCED COGNITIVE DYSFUNCTION IN SWISS ALBINO MICE - N, DIVYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: Amnesia is a medical condition involving the loss of memory. The memory loss is attributed to a number of illnesses or factors including Alzheimer’s disease (AD) and dementia, amnesia is often caused by head injury, brain trauma, or brain surgery. The incidence of amnesia affects only a small percent of the world’s population, the relevant study is becoming increasingly important with the rising numbers of people with AD. Alzheimer’s is predicted to strike 34 million people globally by 2025 and 14 million within the U.S. alone over subsequent 40 years. Methods: The study the possible protective effect of aqueous extract of Citrullus lanatus pulp (ACL) using scopolamine-induced amnesia in Swiss Albino mice. The mice were divided randomly into six groups each of five mice (n=5). Groups IV, V, and VI received mice feed and ACL 25%, 50%, and 100% instead of water for 21 days. Mice of Groups I, II, and III were treated with mice feed and water ad libitum. The animals were subjected to a single dose of scopolamine (1 mg/kg b.wt. ip) except in Group I on the 21st day 60 min after respective drug administration and observed for the effects in brain activity for the learning and memory. The behavioral parameters such as passive avoidance, Morris water maze, Y-Maze, and elevated plus maze were used as a tool for cognitive dysfunction study. Results: The ACL significantly reversed the scopolamine induced amnesia in mice. This is evident as C. lanatus is rich in lycopene content. The experimental models demonstrated that all the concentration of ACL treated mice showed remarkable results in restoring the effect of amnesia induced by scopolamine. Conclusion: To concise, these results suggest that ACL may exhibit protective effect on the brain to reverse the scopolamine induced amnesia. Further, it can be explored extracting the lycopene content of watermelon.